Subtitling cultural-specific items (CSIs): Strategies and quality in Induk Gajah - Alfi Rianis Tsani; Sugeng Hariyanto; Esti Junining (English Learning Innovation, 2026)
In the era of globalization, films served as influential audiovisual media for representing cultural values. However, subtitling Cultural-Specific Items (CSIs) presents linguistic and cultural challenges that affect meaning accuracy and audience acceptability. This study examined how CSIs are represented in the English subtitles of the Indonesian series Induk Gajah, with the aims of classifying the types of CSIs, identifying the subtitling strategies used, and assessing subtitle quality. A descriptive qualitative design with content analysis was employed, drawing on Newmark’s (2010) CSI categories, Pedersen’s (2011) subtitling strategies, and Pedersen’s (2017) FAR model. The analysis identified 149 CSIs across six categories, with personal life (67) and social life (50) being the most frequent, particularly kinship terms, food references, and social expressions rooted in Batak culture. Substitution was the most common strategy (66), followed by retention (25), direct translation (18), omission (17), generalization (14), and specification (9). The findings suggest a dominance of target-language-oriented strategies, prioritizing audience comprehension. Regarding quality, 85 subtitles showed no penalties, while 57 revealed issues with functional equivalence, particularly in culturally dense expressions.